Algeria : Staff Report for the 2001 Article IV Consultation and Post-Program Monitoring Discussion. (IMF Staff Country Reports; Country Report, 2001)
Since the outset of IMF-supported adjustment and reform program, Algeria has made substantial progress toward the restoration of macroeconomic stability and implemented a set of structural reforms. High hydrocarbon prices also contributed to a sharp improvement in the budget position. A prudent fiscal stance and cautious easing of monetary conditions have led to a major strengthening of the balance of payments position and a large accumulation of official reserves. The authorities are urged to enhance transparency and strengthen the efforts to improve governance.